A conserved arginine with non‐conserved function is a key determinant of agonist selectivity in α7 nicotinic ACh receptors. (27th February 2021) - Minguez‐Viñas, Teresa; Nielsen, Beatriz E.; Shoemark, Deborah K.; Gotti, Cecilia; Sessions, Richard B.; Mulholland, Adrian J.; Bouzat, Cecilia; Wonnacott, Susan; Gallagher, Timothy; Bermudez, Isabel; Oliveira, Ana Sofia
Abstract : Background and Purpose: The α7 and α4β2* ("*" denotes possibly assembly with another subunit) nicotinic acetylcholine receptors (nAChRs) are the most abundant nAChRs in the mammalian brain. These receptors are the most targeted nAChRs in drug discovery programmes for brain disorders. However, the development of subtype‐specific agonists remains challenging due to the high degree of sequence homology and conservation of function in nAChRs. We have developed C(10) variants of cytisine, a partial agonist of α4β2 nAChR that has been used for smoking cessation. The C(10) methyl analogue used in this study displays negligible affinity for α7 nAChR, while retaining high affinity for α4β2 nAChR. Experimental Approach: The structural underpinning of the selectivity of 10‐methylcytisine for α7 and α4β2 nAChRs was investigated using molecular dynamic simulations, mutagenesis and whole‐cell and single‐channel current recordings. Key Results: We identified a conserved arginine in the β3 strand that exhibits a non‐conserved function in nAChRs. In α4β2 nAChR, the arginine forms a salt bridge with an aspartate residue in loop B that is necessary for receptor expression, whereas in α7 nAChR, this residue is not stabilised by electrostatic interactions, making its side chain highly mobile. This lack of constrain produces steric clashes with agonists and affects the dynamics of residues involved in agonist binding and the coupling network. Conclusion and Implications: We conclude that the high mobility of the β3‐strand arginine in the α7 nAChR influences agonist binding and possibly gating network and desensitisation. The findings have implications for rational design of subtype‐selective nAChR agents.